Mood disorders are associated with inferior outcomes of anatomic total shoulder arthroplasty. Issue 2 (March 2019) - Eads, Ryan B.; Brolin, Tyler J.; Smith, Richard A.; Azar, Frederick M.; Throckmorton, Thomas W.
Abstract : Background: Mood disorders (MD) have been associated with inferior outcomes after orthopaedic procedures, but little is known about their effect on total shoulder arthroplasty (TSA). Methods: In patients with primary TSA and a minimum of 2 yr clinical and radiographic follow-up, documentation of depression, anxiety, and/or use of a prescription mood-stabilizing drug indicated MD. Prolonged narcotic use was patient-reported consumption at most recent follow-up or filled narcotic prescription within 3 mo in a statewide database. Results: Chronic pain syndromes were more frequent in 24 patients with MD (76%) than in 63 without (1.6%), and narcotic use was higher (54% vs. 13%, respectively). There were no significant differences in range of motion, strength, complications, reoperations, or radiographic complications and none in the amount of improvement for any of the functional parameters. Conclusions: Patients with MD were four times more likely to require narcotics for pain control, although function improved by an amount similar to the control group. Level of evidence: Level III, retrospective comparison study.